KUALITAS KARKAS TERNAK BABI GROWER YANG MENGGUNAKAN TEPUNG KULIT KOPI SEBAGAI PENGGANTI SEBAGIAN DEDAK PADA RANSUM - Gerungan, Magdalena S.; Lapian, Mien Th.R.; Kalele, J.A.D; Poli, Zulkifly (ZOOTEC, 2017)
EFFECT OF COFFEE SKIN FLOUR AS A SUBSTITUTE FOR RICE BRAN IN THE RATION ON CARCASS QUALITY OF GROWER PIGS. Research entitled effect of coffee skin flour in the ration of grower phase pig on slaughter weight, carcass length and carcass percentage have been done. Research conducted for 52 days using 16 Landrace pigs. Methods of randomized block design were used. Four replication as group of weight was used and treatments were four level of coffee skin flour of 0%, 25%, 50%, and 75%. The research variables are slaughter weight, carcass length and carcass percentage. Results of statistical analysis showed that there was no significant difference between treatments and the percentage of carcasses and slaughter weight (P> 0.05). The mean of slaughter weight is 76.68 kg and the average of carcass percentage is 63.80%. Analysis of variance showed that there is highly significant difference (P<0.01) between treatments and the length of carcass. Further test by the least significance difference method indicates that there was no significant difference on carcass length between R0 and R1, R2 and R3. There was also no significant difference on carcass length between R1 and R2, R1 and R3, and R2 and R3. Based on these results, it can be concluded that the use of coffee skin flour as a substitution as much as 25% of in the ration can increase the length of the carcass.Keywords: carcass length and carcass percentage, flour coffee skin, slaughter weight, pork.